Therapists and the Topic of Meaning in Life in Their Encounters With Adolescents With Developmental Trauma: A Qualitative Study - Olstad, Kjersti; Lien, Lars; Leonhardt, Marja; Sørensen, Torgeir; Danbolt, Lars Johan (Frontiers in Psychiatry, 2022)
Background: Meaning in life is important to achieve quality of life, psychological well-being and good mental health. Existential issues such as meaning in life have limited attention in mental health care and treatment for children and young people in Norway. People in crisis often ponder existential questions. We find little research on this topic in relation to therapists who work with adolescents with developmental trauma. The purpose of this study was to examine how meaning in life is understood and addressed from the perspectives of therapists working with adolescents struggling with trauma. Method: The study has a qualitative design, based on focus groups with therapists in mental health care for children and adolescents. The interviews were transcribed and analyzed using systematic text condensation. Results: Therapists had limited professional experience and competence to address and explore meaning as a topic in therapy. Yet there was interest in the topic and a clear expression thought that young people with trauma experience may benefit from the incorporation of meaning perspectives into therapy. Conclusion: Therapists at a mental health outpatient clinic for children and adolescents found the topic of meaning important but challenging to involve in the treatment of adolescents with developmental trauma. There is a need for more research to enhance understanding of what it means to include meaning as a topic in child and adolescent psychiatry, and what may be the specific benefit and challenges involved.